Derivada de la función compuesta.

(1)

0

0

0

0

(2)

x

→a

0

x→a

x→a

x→a

0

0

0

0

1

1

1

0

0

n

n

(3)

n

1

n

1

n

1

n

n

n

1

n

1

0

0

1

n

1

n

0

1

f01(a)

1

1

1

0

1

0

0

0

1

0

f01(a)

f(x)

0

0

f(a)

+

+

0

+

+

0

ff0((aa))

(4)

+

+

g(x)

0

0

0

+

+

+

+

n

n

t1

n

n

tn

n

ynn

n

n

t1

n

tn1

n

n

n

an

a

n

a

ana

n

a

0

x→a

x

a

a

+

0

a

a

+

0

(5)

0

0

0

φ(x)

0

φ(a)

0

0

0

+

+

2

2

2

x

→1+

x→1

(6)

+

+

2

3

1+|2xx|

0+

x

+

2

x

→0

x→0+

x→0

2

1/2

0

0

12

1/2

+

2

2

2

2

(7)

0

0

0

0

2

1/2

2

3

1/3

1/3

1/3

+

0

13

2/3

0

13

2/3

3

3

2

0

2

2

x

→0

x→0 2x 1+x

x→0

x

→0

x→0 2x 1−x

x→0

0

(8)

+

0

a

x

→0

x→0

x→0

φ(x)

0

φ(0)

0

0

12

12

12

12

12

12

0

12

12

+0

0

12

12

0

1 2

+0

1 2

2

3

(9)

n

n

2n

2

n

n

3n

3

2

3

n

n

n

2

x→0

0

2

0

+

0

1

1+x

x→0+

x→0

x→0

x

→0

x→0+

x→0+

(10)

x→0+

1/x

1x

+

x

→0+

1/x

y→+

y

x

→0+

1/x

x→0+

x→0+

x

→0

x→0+

0

p

0

p1

p1

p

p+1

p+1

x

→0

x→0

p

x

→0

x→0

p

x→0

p1

0

(11)

x

1

1

0

1

0

x

y

1

0

x

1

1

0

f01(a)

a

1

0

f01(0)

12

a

1

0

f01(1)

1+1e

Actualización...

Referencias

Related subjects :